MENINGKATKAN KESEIMBANGAN BERJALAN MELALUI BERMAIN BAKIAK PADA ANAK TUNAGRAHITA SEDANG - Cica Idrus; Fatmawati Fatmawati; Markis Yunus (Jurnal Penelitian Pendidikan Khusus, 2012)
The research was motivated by the problems that researchers found in the field. Identification and assessment of results, the child has a disorder on the balance runs (usually a straight forward way). Thus the researchers help to improve balance through play clogs. This study aims to prove that by playing clogs can improve balance walking (ordinary road straight ahead) in children Tunagrahita is X. Based on the results of this study shows that the ability to walk the balance (usually a straight forward way) children can be improved through the playing of clogs. At baseline conditions in the seven-time observation dilakuakan children can run balanced in two steps, the intervention conditions increased the ability of the child is a child could run balanced as much as 5 steps. This means that hypothesis is accepted for data analysis between the estimated state has a tendency toward (+), the stability trend variable, the trace data and the increased level changes in a positive and overlope data on the condition of the smaller (0%). Means playing clogs can improve walking balance in children is a class trunagrahita DI / CI in SD N stars. 35 (SDLB) North Painan. Of this study is expected to be useful for teachers, parents, researchers use to play next to clogs in improving walking balance in children Tunagrahita is another